Pendampingan Budaya Religius Melalui Sholat Dhuha Dalam Penguatan Karakter Peserta Didik di MA Nurul Huda Sedati Sidoarjo - Siti Kholidatur Rodiyah; Laila Badriyah; Eli Masnawati (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Strengthening students' religious character has become a strategic priority in Islamic education, particularly amid the increasingly complex social, cultural, and technological developments that influence young people's attitudes and behavior. These challenges require educational institutions to move beyond academic achievement and place greater emphasis on character development grounded in religious values. One effective approach is the cultivation of a religious culture through structured and sustainable worship practices within the school environment. This community service program aimed to assist the implementation of a religious culture through the habituation of Dhuha prayer in strengthening students’ character at MA Nurul Huda Sedati Sidoarjo. The program employed a participatory mentoring approach integrated with habituation and role-modeling strategies. The implementation process consisted of needs assessment, mentoring of congregational Dhuha prayer activities, observation, reflection, and evaluation. The findings revealed that continuous and intensive mentoring significantly increased students’ participation in Dhuha prayer and fostered stronger self-awareness in performing religious practices. Furthermore, the program contributed to the development of religious character values, including discipline, responsibility, independence, honesty, and social awareness. The initiative also strengthened the religious culture within the madrasa and promoted a more supportive educational environment for character formation. Therefore, the habituation of Dhuha prayer, supported by consistent mentoring and teacher role modeling, can serve as an effective and sustainable strategy for reinforcing students’ religious character.